Development and Validation of an Electronic Medical Record–Based Algorithm to Identify Patient Milestones in the Hepatitis C Virus Care Cascade. (3rd July 2018) - Zucker, Jason; Aaron, Justin G; Feller, Daniel J; Slowikowski, Jacek; Evans, Henry; Scherer, Matthew L; Yin, Michael T; Gordon, Peter
Abstract: Disease-specific care cascades are important public health and organizational tools to characterize gaps in care and target resources, but they are labor-intensive to maintain. Using data available from the electronic medical record, we developed an algorithm with high accuracy for correctly representing an individual's status in the hepatitis C virus care cascade.